2016
DOI: 10.1073/pnas.1519998113
|View full text |Cite
|
Sign up to set email alerts
|

Hedonism and the choice of everyday activities

Abstract: Most theories of motivation have highlighted that human behavior is guided by the hedonic principle, according to which our choices of daily activities aim to minimize negative affect and maximize positive affect. However, it is not clear how to reconcile this idea with the fact that people routinely engage in unpleasant yet necessary activities. To address this issue, we monitored in real time the activities and moods of over 28,000 people across an average of 27 d using a multiplatform smartphone application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 28 publications
3
49
0
3
Order By: Relevance
“…Mood fluctuates throughout the day as well as the lifespan, though overall most individuals feel "fine" most of the time (Taquet et al, 2016). At one time or another, however, virtually everyone will experience low mood that is significant enough to endorse one or more symptoms of depression.…”
Section: Subjective Memory Complaints and Memory Performance In Negatmentioning
confidence: 99%
“…Mood fluctuates throughout the day as well as the lifespan, though overall most individuals feel "fine" most of the time (Taquet et al, 2016). At one time or another, however, virtually everyone will experience low mood that is significant enough to endorse one or more symptoms of depression.…”
Section: Subjective Memory Complaints and Memory Performance In Negatmentioning
confidence: 99%
“…Mood fluctuates throughout the day as well as the lifespan, though overall most individuals feel ‘fine’ most of the time (Taquet et al 2016 ). At one time or another, however, virtually everyone will experience low mood that is significant enough to endorse one or more symptoms of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, engaging in distraction tactics provides hedonic benefits only for a limited period of time (e.g., Kross and Ayduk 2008). There is also evidence indicating that watching TV leads to small, short-term increases in happiness (Taquet et al 2016) and relaxation (Kubey and Csikszentmihalyi 1990), but these feelings of relaxation tend to go away after TV viewing ends. These findings are consistent with past work indicating that effects of positive affect are short-lived (Bachmann et al 2018;Sheldon et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Past work shows that individuals prefer familiar activities when they are under time or performance pressure (Litt et al 2011) and engage in behaviors aimed at maintaining a sense of meaningfulness and predictability when they feel threatened (Proulx and Heine 2006). So individuals might prefer the familiarity and predictability of TV viewing over any other activity when they feel lower PA. Providing preliminary evidence for this possibility, individuals were found to prefer engaging in pleasant activities (including watching TV) when they feel unhappy (Taquet et al 2016). Although not directly manipulating or measuring affect, past experimental work also found that individuals turn to TV when they go through an experience that likely disrupts their PA-that is, when they receive negative (vs. positive) performance feedback on a test (Moskalenko and Heine 2003).…”
Section: Introductionmentioning
confidence: 98%